Perception on quality of life at work from drivers of urban transport - Oviedo Oviedo, Nancy Viviana; Sacanambuy Cabrera, José Manuel; Matabanchoy Tulcan, Sonia Maritza; Zambrano Guerrero, Christian Alexander (Universidad y Salud, 2016)
Introduction: Quality of working life in organizations is a transversal aspect in the management of human talent, since this area not only implements, maintains and improves quality management systems and processes of service provision, but also focus its intervention on the human component. Objective: Characterize the quality of working life through the processes of human talent management of the Strategic System of Public Transport in the city of Pasto. Materials and methods: Therefore, a quantitative paradigm of a descriptive type was used in order to identify, describe and analyze the quality of work life through health, well-being and perception of work, with the participation of 468 drivers. The methods used for data collection were bibliographic review, a Likert-type attitude scale and a self-report questionnaire for morbidity. The results of these applications were systematized using the statistical software IBM SPSS Statistics. Results: Within this population there is a favorable attitude towards their health conditions (79.3%); however, these self-reports show the presence of physical pains that affect the health of workers (back pains, waist and hands), a very favorable attitude when facing the labor welfare (77.6%) and a very favorable attitude towards the perception of work (75.2%). Conclusions: The results allow to identify the areas to be strengthened: promoting the drivers’ quality of life (occupational health, labor well-being and job perception), improving provision of service and promoting the development of the city where the labor of the organizational psychologist is highlighted within the company.